2006
DOI: 10.1212/01.wnl.0000219620.69618.9d
|View full text |Cite
|
Sign up to set email alerts
|

Detection of intracranial venous reflux in patients of transient global amnesia

Abstract: Retrograde intracranial venous flow caused by left brachiocephalic vein occlusion was found only in patients with transient global amnesia (TGA). This result suggests that TGA patients may have an underlying impairment of cerebral venous outflow that increases their vulnerability to TGA attack.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
1
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(60 citation statements)
references
References 26 publications
3
51
1
5
Order By: Relevance
“…Our findings are similar to those reported by other authors using similar or other methods of evaluation. [17][18][19][20]22 In this prospective study, we followed standardized criteria for the assessment of patients with TGA and controls, and every subject was evaluated by an experienced neurologist.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are similar to those reported by other authors using similar or other methods of evaluation. [17][18][19][20]22 In this prospective study, we followed standardized criteria for the assessment of patients with TGA and controls, and every subject was evaluated by an experienced neurologist.…”
Section: Discussionmentioning
confidence: 99%
“…Diencephalic structures involving the hippocampus may play a substantial role in the pathophysiology of TGA. Using time-of-flight magnetic resonance angiography, Chung et al 17 found intracranial venous reflux in a group of patients with TGA. This finding supports the hypothesis that retrograde venous hypertension causing transient cerebral venous ischemia is important in the pathogenesis of TGA.…”
mentioning
confidence: 99%
“…25 Other entities like transient global amnesia and chronic migraine have also been associated with jugular reflux and changes in the venous dynamics. 26,27 Additionally, well-known MS susceptibility factors like cardiovascular, infectious, and inflammatory risks have been associated with increased prevalence of CCSVI. 28 The paucity of differences in any of the conventional inflammatory outcome measures may be explained by the recent findings, which suggest that the cortical atrophy, and specifically cortical hemispheric volume loss lateralization, could influence the homeostasis of autonomic nervous system (ANS).…”
Section: Discussionmentioning
confidence: 99%
“…Various causes have been hypothesized including ischemia, epilepsy, migraine [119] and disturbance of cerebral venous blood flow, [120] leading to ischemia of structures such as the hippocampus that are involved in memory. [121] There has been no scientific proof of any cause. However diffusion weighted MRI studies taken from 12-24 hours following an episode has shown there to be small dot-like lesions in the hippocampus.…”
Section: Transient Global Amnesiamentioning
confidence: 99%